Regulatory T cells (Tregs): A major immune checkpoint to consider in combinatorial therapeutic HIV-1 vaccines - Audrey Hubert; Nabila Seddiki (Taylor & Francis Group, 2018)
The field of immunotherapeutics is living an exceptional time as new antibodies that take brakes off T-cells and unleash them on tumours are being approved by the US-Food and Drug Administration (FDA). For the design and development of an HIV-1 therapeutic-vaccine, one would need preferably to shift the balance T-effectors/T-regulatory cells (Teff/Tregs) towards effectors to improve vaccine-specific immune-responses. Given the success with the new immune-checkpoint-blockers (ICB), it is an appropriate time for HIV-1 field to seize this opportunity and develop new therapeutic vaccine-strategies that take into consideration ICB and other immunomodulators such as cytokines. While the vaccine is important to stimulate HIV-1-specific T-cell responses, cytokines will support the expansion of the stimulated virus-specific T-cells and ICB will reverse exhaustion and unchain cytotoxic T-cells. In this commentary, we will spotlight Tregs as another major brake for T-cell immunity and address the main stumbling-blocks that often blurs HIV-1-specific-Tregs status with regards to their role (beneficial or detrimental) and we will recall some proof-of-concept studies where therapeutic immunization skewed the HIV-1-specific response from Tregs to Teffs which impacts on the magnitude of viral replication. We will also suggest some strategies to shift the balance towards Teffs and potentiate HIV-1-specific immune-responses.